The Atacama Cosmology Telescope: cosmological parameters from three seasons of data - Sievers, J; Hlozek, R; Nolta, MR; Acquaviva, V; Addison, G; Ade, P; Aguirre, P; Amiri, M; Appel, J; Barrientos, L; Battistelli, E; Battaglia, N; et al. (2013)
We present constraints on cosmological and astrophysical parameters from high-resolution microwave background maps at 148 GHz and 218 GHz made by the Atacama Cosmology Telescope (ACT) in three seasons of observations from 2008 to 2010. A model of primary cosmological and secondary foreground parameters is fit to the map power spectra and lensing deflection power spectrum, including contributions from both the thermal Sunyaev-Zeldovich (tSZ) effect and the kinematic Sunyaev-Zeldovich (kSZ) effect, Poisson and correlated anisotropy from unresolved infrared sources, radio sources, and the correlation between the tSZ effect and infrared sources. The power ℓ2Cℓ/2π of the thermal SZ power spectrum at 148 GHz is measured to be 3.4±1.4 μK2 at ℓ = 3000, while the corresponding amplitude of the kinematic SZ power spectrum has a 95% confidence level upper limit of 8.6 μK2. Combining ACT power spectra with the WMAP 7-year temperature and polarization power spectra, we find excellent consistency with the LCDM model. We constrain the number of effective relativistic degrees of freedom in the early universe to be Neff = 2.79±0.56, in agreement with the canonical value of Neff = 3.046 for three massless neutrinos. We constrain the sum of the neutrino masses to be Σmν < 0.39 eV at 95% confidence when combining ACT and WMAP 7-year data with BAO and Hubble constant measurements. We constrain the amount of primordial helium to be Yp = 0.225±0.034, and measure no variation in the fine structure constant α since recombination, with α/α0 = 1.004±0.005. We also find no evidence for any running of the scalar spectral index, dns/dln k = -0.004±0.012. © 2013 IOP Publishing Ltd and Sissa Medialab srl.